Refluxo gastroesofágico em cadelas submetidas a ovariohisterectomia convencional ou videoassistida sob diferentes medicações pré-anestésicas - Hartmann, Hellen Fialho (2016)
The gastroesophageal reflux disease arises from the gastroduodenal content flow to the esophagus and/or associated organs, which leads to wide range of clinical signs and disease. The pulmonary aspiration of gastric contents is a major cause of post-anesthethic morbidity and mortality. Another gastroesophageal reflux disease's consequence in dogs is esophageal stenosis, whose treatment is expensive and sometimes associated to bad prognosis. It is unknown the incidence of intraoperative reflux in canine. There are occurrence reports of this event in conventional and video-assisted surgeries. Our objetive, by executing this project, using flexible endoscopy, was to assess the presence and to quantify gastroesophageal reflux in dogs undergoing ovariohysterectomy using different analgesic protocols - morphine, tramadol and methadone, and different surgical approaches - conventional and video-assisted. In the first work presented, two groups of dogs receiving the same anesthetic protocol, were submitted to ovariohysterectomy (conventional and video-assisted), noting that in the second group the incidence of intraoperative gastroesophageal reflux was higher, as well as severity of the event. In the second study, three groups of dogs undergoing conventional ovariohysterectomy, received different pre-anesthetic drugs - morphine, tramadol and methadone. There were not significant differences between groups, and the three of them occurred intraoperative gastroesophageal reflux. It was concluded that the video-assisted surgery resulted in a higher incidence and greater severity of intraoperative gastroesophageal reflux than conventional in patients undergoing anesthetic protocol tested. The creation of the pneumoperitoneum, the decubitus changes and the association between pneumoperitoneum and morphine were assigned as likely triggers of gastroesophageal reflux in the first experiment. The use of different drugs in pre-medication bitches submitted to conventional ovariohysterectomy caused no increased incidence of gastroesophageal reflux, however morphine administration increased the incidence of preoperative emesis. It was also found that the reflux in different intensities are commonly observed in practice conventional or video-assisted ovariohysterectomy.